1999
DOI: 10.1136/oem.56.11.774
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence of childhood cancer in the West Midlands of the United Kingdom in relation to proximity to main roads and petrol stations.

Abstract: Objectives-To investigate whether there is an excess of leukaemias in 0-15 year old children among those living in close proximity (within 100 m) of a main road or petrol station. Methods-Data for 0-15 year old children diagnosed between 1990 and 1994 in the United Kingdom West Midlands were used. Postcode addresses were used to locate the point of residence which was compared with proximity to main roads and petrol stations separately, and to both together. Odds ratios (ORs) were calculated with solid tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 20 publications
0
80
1
5
Order By: Relevance
“…Elevated risks of childhood cancer were associated with several surrogate measures of vehicle exhaust exposure, including traffic volume, car density, estimated concentration of nitrogen dioxide in outdoor air and proximity to sources of vehicle exhaust (Savitz and Feingold, 1989;Knox and Gilman, 1997;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000). Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated risks of childhood cancer were associated with several surrogate measures of vehicle exhaust exposure, including traffic volume, car density, estimated concentration of nitrogen dioxide in outdoor air and proximity to sources of vehicle exhaust (Savitz and Feingold, 1989;Knox and Gilman, 1997;Nordlinder and Jarvholm, 1997;Feychting et al, 1998;Harrison et al, 1999;Pearson et al, 2000). Recent studies in California evaluating childhood cancer and traffic density have generally found no association (Reynolds et al, 2001;Langholz et al, 2002;Reynolds et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the study design, the cases were more mobile than controls and full adjustment for this bias is difficult to achieve. Harrison et al (1999) found a nonsignificant excess of leukaemia among children living within 100 m of a main road or petrol station. Best et al (2001), using different methods from ours and a range of models, found a consistent positive association between risk of childhood leukaemia and atmospheric benzene levels in Greater London in the years 1985 -1996, the areas with highest risk being clustered in Inner London.…”
Section: Discussionmentioning
confidence: 90%
“…29,30 However, studies of other health outcomes, such as asthma hospitalizations and medication use and risk for various cancers, have provided less consistent evidence. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Evidence also suggests that traffic density 49 and traffic proximity 50 may be linked to adverse preterm birth outcomes.…”
Section: Near-roadway Traffic and Healthmentioning
confidence: 99%